Electron microscopy in the diagnosis of viral gastroenteritis in hospitalised children in the Czech Republic - Arientova, Simona (Folia Microbiol (Praha), 2012)
Our study has been aimed at demonstrating the main role of viruses in the aetiology of acute gastroenteritis in children less than 5 years old and at pointing out the diagnostic potential of electron microscopy in the diagnosis of viral gastroenteritis. A prospective study was conducted to analyse the aetiology of diarrhoeal diseases in children less than 5 years of age admitted to the Department of Infectious Diseases between September 2006 and December 2008. All children were tested by faecal culture, latex agglutination and electron microscopy. A total of 832 children were included in the study. An aetiological agent was detected in 788 children (94.6 %). A bacterial aetiology was found in 22 (2.6 %) children and bacterial–viral co-infection was found in 146 (17.6 %) patients. The most frequent causative agents of gastroenteritis in children were viruses, which were detected in 620 (74.5 %) patients. The main causes of viral gastroenteritis were rotaviruses (detected in 410 children), followed by caliciviruses (42), coronaviruses (28), adenoviruses (19) and astroviruses (14). Dual viral infections were detected in 107 children, with rotavirus–calicivirus co-infection being the most common. Electron microscopy proved to be a more sensitive method in comparison with the latex agglutination test for the diagnosis of rotaviruses and adenoviruses. The major role of viruses in diarrhoeal diseases among children under 5 years of age in the Czech Republic has been confirmed. The diagnostic potential of electron microscopy, particularly in small outbreaks of gastroenteritis, was clearly shown.